Development of solar powered water treatment device (SWAD) prototype - Ismail I.N.B.; Khean F.F.; Zawawi M.H.; Zahari N.M.; Abidin S.Z.; Yusairah W.N.; Zuhdi A.W.M.; Eqwan M.R.; Mohamed H.; Ramli M.Z.; Mansor M.H.; Syaifoelida F.; et al. (American Institute of Physics Inc., 2023)
Water is the most essential element for life, there are still some remote areas in Malaysia where clean freshwater is not accessible, this problem had troubled the locals for decades. Solar powered water treatment device is basically a floating water filter which operates in a self-sustainable way on calm water body such as lake. The pumps used for the device will obtain the energy from the solar panel to pump water into the filter. For this project, the device is being tested at the UNITEN lake. The main objective of development solar powered treatment device prototyope (SWAD) is to improve the water quality by selecting a suitable water filter while the device is supported by a stable structure. The project undergoes preliminary design, CAD drawings with simulation, prototype fabrication and prototype testing. The structure of the device is made of combination aluminium which is light weight, sturdy and not reactive to water. The solar panel that has been selected is rated at 250W and it is sufficient to power four pumps rated at 30W. 2019 Author(s).